Target current: a useful parameter for characterizing laser ablation. (13th February 2017) - Krása, J.; Giuffreda, E.; Delle Side, D.; Nassisi, V.; Klír, D.; Cikhardt, J.; Řezáč, K.
Abstract: A current flowing between the ground and target exposed to the nanosecond laser radiation is analyzed to complete characteristics of laser ablation. Three phases of the target current are distinguished. During the ignition phase, the electron emission is driven by the laser pulse and the positive charge generated on the target is balanced by electrons coming from the ground through the target holder. At post-pulse times, a peaked waveform of the target current is typical for the active phase of the plasma and can give information on the material composition of the ablated surface layers. The afterglow phase is determined by a current of electrons flowing from the target to the ground. Experiment shows that the time-resolved target current is very sensitive to the actual composition of the surface layer of irradiated target and laser parameters.